Legal and ethical issues in knowledge management in Malaysia - Abdul Ghani Azmi, Ida Madieha (Elsevier, 2010)
In this era of k-economy, knowledge management is becoming crucial to take stock of the influx of knowledge available on the Internet as well as consolidating knowledge generated within an organization. This paper explores the legal and ethical ramifications of all the various processes of knowledge management from capturing, creation, sharing and dissemination of knowledge within an organization in Malaysia.